Les reconfigurations de la posture de chercheuse en période de confinement : une ethnographie impliquée au Secours populaire français - Alizé Cavé (Anthropologie & Santé)
Based on a doctoral study of a federation of the French charity “Secours populaire”, this article examines how the lockdown led to reconfigurations of the researcher's posture in the field, by allowing her to move from participant observation to observer participation. Secondly, the article analyzes how these reconfigurations produced new knowledge about the association. This new knowledge is linked to the revelation of the mechanisms of domination of the volunteers over the beneficiaries, and particularly of the “food violence”, “discretionary power” and “erosion of emotions” that were exacerbated during lockdown.